Uji Daya Hambat Ekstrak Lengkuas (Alpinia galanga) Terhadap Pertumbuhan Jamur Candida albicans - Yuma Ardian Allu; Siti Nuryanti (Universitas Tadulako, 2022)
Galangal (Alpinia galanga) is a nutritious plant that can cure various diseases. This part of the plant, such as the rhizome, functions as a traditional medicine. This study aims to determine the inhibition of the fungus Candida albicans using galangal extract. Galangal extract was made using three different kinds of the solvents, namely hexane, ethyl acetate, and methanol. The suspension of Candida albicans fungus was obtained from the Biology Laboratory, FMIPA, Tadulako University. Fungal test using the well method. The results showed that the inhibitory power of galangal extract against the growth of Candida albicans using ethyl acetate and methanol was greater than that of hexane. Based on observations, the percentage of inhibitory power of galangal extract on the growth of Candida albicans with hexane, ethyl acetate, and methanol as solvents was 0% for hexane, 1,70% for ethyl acetate, and 4,70% for methanol.